*Relationship between atrophic gastritis, intestinal metaplasia, dysplasia and Helicobacter pylori infection - Fikret DEMİRCİ,; Kaya ÖZÇIRPICI,; Suna ERKILIÇ,; Vahap OKAN,; Mustafa ARAZ,; Şebnem AKTARAN, (Turkish Journal of Gastroenterology, 2019)
-